Joubert syndrome: a rare disorder case report - Mehta, Rachna S.; Saxena, Amit; Sonawane, Vijay B.; Jatoo, Zameer Ahmed; Archana, V. (International Journal of Contemporary Pediatrics, 2025)
Joubert syndrome (JS) is a rare neurodevelopmental disorder characterized by hypotonia, ataxia, and delayed developmental milestones. In some cases, disorders related to JS may involve other organ systems beyond the central nervous system, potentially resulting in multi-organ dysfunction. We describe a patient with pure JS who had ataxia, reduced muscular tone, and developmental delay. A provisional diagnosis was established based on the detection of the characteristic molar tooth sign on magnetic resonance imaging. Genetic testing subsequently confirmed the diagnosis. The patient was managed conservatively with supportive symptomatic treatment. Although rare, JS can present with systemic involvement affecting multiple organs, necessitating comprehensive evaluation and management. Therefore, whenever an infant exhibits the previously stated neurodevelopmental symptoms, doctors should always keep this medical condition in mind.